2023
DOI: 10.1128/mbio.03085-22
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Energy-Coupling Factor Transporter Subunits Enable Flavin Acquisition and Extracytosolic Trafficking for Extracellular Electron Transfer in Listeria monocytogenes

Abstract: Bacteria import vitamins and other essential compounds from their surroundings but also traffic related compounds from the cytosol to the cell envelope where they serve various functions. Studying the foodborne pathogen Listeria monocytogenes , we find that the modular use of subunits from a prominent class of bacterial transporters enables the import of environmental vitamin B 2 cofactors and the extracytosolic trafficking of a vitamin B 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…We performed comparative genomic analyses mining apbE gene clusters that lack a known electron transfer mechanism and found that a transmembrane protein with a DUF4405 domain of unknown function frequently colocalized with apbE in Proteobacteria and Firmicutes species ( Figure 5B ). Consistent with these DUF4405s functioning in flavinylation-based electron transfer, we observed gene clusters containing apbE and DUF4405 genes also often encoded genes for a flavinylated Flavodoxin and a transporter that provisions Listeria monocytogenes with extracytosolic flavins ( Figure 5C ) (Rivera-Lugo et al 2023).…”
Section: Resultsmentioning
confidence: 53%
“…We performed comparative genomic analyses mining apbE gene clusters that lack a known electron transfer mechanism and found that a transmembrane protein with a DUF4405 domain of unknown function frequently colocalized with apbE in Proteobacteria and Firmicutes species ( Figure 5B ). Consistent with these DUF4405s functioning in flavinylation-based electron transfer, we observed gene clusters containing apbE and DUF4405 genes also often encoded genes for a flavinylated Flavodoxin and a transporter that provisions Listeria monocytogenes with extracytosolic flavins ( Figure 5C ) (Rivera-Lugo et al 2023).…”
Section: Resultsmentioning
confidence: 53%
“…This is probably because there are many variations in EET gene configuration among members of the phylum Bacillota. Variations in the configuration of EET genes have been reported [16,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…83 Recombinant reductase production and purification Hexa-histidine-tagged reductase constructs were expressed in E. coli Rosetta cells using either the pET28a or pMCSG53 expression vectors, as previously described. 84 Briefly, expression was performed using 500 mL cultures of Luria-Bertani broth (BD LB Broth, Miller #244610) + 100 µM riboflavin, grown to an OD of 0.7-1.0 at 37 °C, then induced with 1 mM β-d-1-thiogalactopyranoside overnight at 20 °C. Kanamycin (30 mg/mL, pET28a vector) or carbenicillin (100 mg/mL, pMCSG53 vector) were used for selection.…”
Section: Proteomics Mass Spectrometrymentioning
confidence: 99%